ショウワキチ タテモノ ノ フネンカ ニ トモナウ コウゾウ ザイリョウ トシテ ノ セッコウ ノ リキガクテキ トクセイ - 佐藤, 稔夫; サトウ, トシオ; 平山, 善吉; ヒラヤマ, ゼンキチ; 岡田, 満; オカダ, ミツル; Sato, Toshio; Hirayama, Zenkichi; Okada, Mitsuru (1982)
P(論文) 南極昭和基地で使用する構造材料の選定について, 主材料を石膏に設定し, その性質について, 低温(-20℃)から常温(+20℃)までの諸性能を調べた。また, 鉄筋補強軽量石膏部材の, 構造材料としての有用性を総合的に把握するため, 梁, 柱およびラーメンの構造実験を行い, あわせて同一供試体のコンクリート, あるいは, 鉄筋コンクリート部材と比較して, その挙動を調べ, それぞれについて実験値と理論値を比較考究した。以上の実験から次の結果を得た。(1)低温に対して優れた特性がある。(2)複合材料としては, 軽量骨材および異形鉄筋との組み合わせに, 優れた機能を発揮する。(3)鉄筋補強軽量石膏部材を構造部材として使用した時, 比強度が大きい。(4)復元力特性および破壊性状ともに, 鉄筋コンクリート部材とほぼ同じような性能を示した。 On the occasion of selecting structural materials for constructions at Syowa Station in Antarctica, the authors considered that gypsum was the most promising one as the main structural material and investigated its mechanical performance over a wide range of temperatures between -20℃(lowest) and +20℃ (normal). The purpose of this paper is to confirm the possibility of applying gypsum to construction. Therefore, the test program was made for beams, columns and framed structures of gypsum. In addition to it, the same test program was made for concrete and reinforced concrete members in order to compare those results. Furthermore, the comparative study of the test values and theoretical ones was conducted. The following conclusions were obtained from the above-mentioned experimental study. (1) Gypsum shows good performance against low temperatures. (2) It fulfills mechanical functions well as a composite material combined with light gravels and deformed bars. (3) Reinforced gypsum members give relatively high strengths as the structural members. (4) Reinforced gypsum members show similar restoring-force characteristics and failure mechanism to those of reinforced concrete members. departmental bulletin paper